Uji Daya Hambat Minyak Atsiri Rimpang Kencur (Kaempferia galanga Linn) Terhadap Trichophyton mentagrophytes, Trichophyton rubrum - Nilda Lely; Dora Rahmanisah (Faculty of Mathtmatics and Natural Sciences, 2017)
The rhizome oil of galanga (Kaempferia galanga L.) was investigated for the antifungal activities against two dermatophytes (Trichophyton mentagrophytes and Tricophyton rubrum). The essential oil of rhi-zome of galanga obtained by steam distillation method was 0,465 (v/w). The antifungal testing was carried out by using agar diffusion method. 1%, 0,5%, 0,25%, and 0,1% were the used concentrations in this research. In a consentrations of 1% the rhizome oil of galanga had an average diameter of inhibition against Trichophyton mentagrophytes 11.8 ± 0.26 mm and a concentration of 0.5% have a diameter of inhibitory average of 7.93 ± 0.20 mm. Essential oils kencur (Kaempferia galanga L.) at a concentration of 1% had an average diameter of inhibition against Trichophyton rubrum 10.37 ± 0.25 mm ±, at a concentration of 0.5% have a diameter of in-hibition of 7.7 ± 0.2 mm.In 0,25% and 0,1% concentrations of essential oil of galanga showed no antifungal activity to T.mentagrophytes, T.rubrum.The chemical composition of the active essential oil was investigated by gas chromatography and mass spectrometry (GC-MS). The major chemical constituents were identified as ethyl cinnamate (65,98%) and ethyl p-metoxycinnamate (23,65%).